Efektivitas Penerapan Bayar Pascapanen pada Pengembalian Pembiayaan Akad Murabahah Pertanian Padi di Baitul Maal wa Tamwil As Salam, Kramat, Demak - Nana Rodiana; Nunung Nuryartono; Salahuddin El Ayyubi (Department of Islamic Economics, IPB University, 2014)
Agricultural crops greatly depends on the season, since the time of land preparation to harvest. Planting delays due to lack of capital, will result in crop failure or low crop productivity. Islamic microfinance institutions, such as BMT, offersmurabaha financing as one of financing options. Application of murabahais generally followed by monthly installment payments. The condition of most farmers doesn’t enable them to have enough income due to pay the main installments with a monthly period. Postharvest payment return system is an alternativemain return of financing. The research result showed the factors that influence farmers in choosing the monthly payment system and postharvest margins on murabaharice farming financing in BMT As Salam, Kramat, Demak using binary logistic regression. The analysis result showed the reason for choosing the payment system significantly influenced rice farmers choice. The chance of postharvest payment is acceptableaccording to the ability of most farmers. The effectiveness of postharvest payment return implementationonmurabaha rice farming financing was measured using a Likert scale. The results showed that postharvest paymentimplementation has been effective in all stages of financing and made a positive impact on farm members.